UPAYA GANTI RUGI AKIBAT TIDAK SAHNYA PENANGKAPAN DAN PENAHANAN PASCA DIKELUARKANYA PERATURAN PEMERINTAH NO. 92 TAHUN 2015 TENTANG PELAKSANAAN KUHAP - Heri Purwanto (Jurnal Media Hukum, 2016)
The point of research is compensation, so the aim of this research was to determine claims for losses due to it unlawful arrest and detention through the pretrial process. This research uses yuridis normative law research analyst with using approach of law (statute approach) and conseptual approach so it’s using the secondary dates sources such as primary,secondary and tertiary legal materials. Dates was collected with library research and analyzed by deductive logic. That the point to research about the compensation due to the implementation of the demands it unlawful arrest and detention through the pretrial process. Basic legal arrangement which is used to determine the pretrial process is the Code of Criminal Procedure (Criminal Procedure Code). The results showed that to know whether the Government Order No. 92. 2016 on implementing the Criminal Code relating to the increase in the amount of compensation can be implemented with a simple process in accordance with the principles of simplicity and fairnes. Based on the results of research and discussion in mind that the process of implementation efforts related to the costs of compensation for damages can not be done easily, because they still have to refer to the decision of the Minister of Finance 983 / KMK.01 / 1983 that was already in need of revision due to too many stages that resulted the process becomes long in accordance with Government Regulation No. 92. 2015 which requires in Article 11, paragraph 2, which reads "Payment of compensation be made within 14 (fourteen) working days from the date of claim for damages is accepted by the minister who organized". The important thing from this research is to porpose immediately change the Indonesian Minister of Finance decision No. 983/KMK.01/198, into new decision implementing government regulation No.92. 2015. So in this case it mean that the proces of disbursement of compensation must be implemented is easy and quick short.